Pengaruh Kualitas Pelayanan Terhadap Loyalitas Konsumen dengan Kepuasan Sebagai Variabel Moderasi: Studi pada Konsumen Kopi Story UNS Surakarta - Ayugita, Camalin; Safitri, Melia; Permata Hati, Viksa Adhellia; Rahadhini, Marjam Desma (Lembaga Pengembangan Kinerja Dosen, 2025)
Coffee shops have become an integral part of modern lifestyle in Indonesia, particularly among the youth. With customer satisfaction as a moderating variable, this study aims to investigate the impact of service quality on customer loyalty, focusing on customers of Kopi Story UNS in Surakarta. A quantitative approach was employed using MRA (moderated regression analysis), involving a sample of 55 respondents. Research instruments were tested for validity and reliability; all indicators were declared valid (r > 0.273) and reliable. The results revealed that service quality had no direct effect on loyalty (t = -0,925; p = 0.359), while customer satisfaction significantly influenced loyalty (t = 0,271; p = 0.006). The interaction between service quality and satisfaction did not show a significant moderating effect (t = 0.946; p = 0.349). The regression model demonstrated good significance (F = 5.767; p = 0.002), explaining 20,9% of the variance in customer loyalty. These findings suggest that customer satisfaction plays a more critical role than service quality in fostering loyalty, emphasizing the importance of strategies to improve satisfaction to enhance long-term loyalty.